n=1

left = 1/2 < 1/sqrt(2)

assume the inequality hold for n=k, denote the left side as s(k), then we have s(k)<1/sqrt(k+1)

n=k+1, the left side

s(k)*(2k+1)/(2k+2)<1/sqrt(k+1) *(2k+1)/(2k+2) = 1/sqrt(k+1) *(2k+2)/(2k+3)

=2sqrt(k+1)/(2k+3)

=2sqrt(k+1)/(k+1+k+2) = 2/(sqrt(k+1)+(k+2)/sqrt(k+1))< 2/{2sqrt(sqrt(k+1)*k+2)/sqrt(k+1))}

= 1/sqrt(k+2)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up